CONTROL AND SUPPORT OF THE QUALITY OF SERVICE IN THE VOIP NETWORK - KOVALENKO, OLEKSANDR; BONDARENKO, VIKTOR; BONDARENKO, NATALIIA (Herald of Khmelnytskyi National University. Technical sciences, 2023)
An approach to the quality of service control and support is proposed, which consists in adding one more indicator to the monitoring of the most used quality indicators – the Network Effectiveness Ratio. The Network Effectiveness Ratio is developed to exclude user behavior and better represent the net performance of the network. Monitoring of this indicator increases the reliability of determining the time interval in which the critical moment of the dynamics of service quality changes is approaching. Missing a critical moment of performance degradation means losing the level of service quality that customers pay for. Therefore, the deterioration of service quality indicators, which indicates the possibility of a critical moment, requires the implementation of certain administrative actions. One of the options for such actions is to run the algorithm for choosing the best route, which controls call routing. The algorithm requires a certain amount of calculations in real time, which creates an additional computational load. The proposed approach due to the control of an additional indicator increases the level of confidence that the dynamics of changes in quality indicators require additional calculations to change routing, which in turn allows support the quality of service at the appropriate level.
Keywords: VoIP network; quality of service; call routing